Current status and challenges of cytokine pharmacology - Zídek, Z; Anzenbacher, P; Kmonícková, E (British journal of pharmacology, 2009)
The major concern of pharmacology about cytokines has originated from plentiful data showing association between gross changes in their production and pathophysiological processes. Despite the enigmatic role of cytokines in diseases, a number of them have become a subject of cytokine and anti-cytokine immunotherapies. Production of cytokines can be influenced by many endogenous and exogenous stimuli including drugs. Cells of the immune system, such as macrophages and lymphocytes, are richly endowed with receptors for the mediators of physiological functions, such as biogenic amines, adenosine, prostanoids, steroids, etc. Drugs, agonists or antagonists of these receptors can directly or indirectly up- and down-regulate secretion of cytokines and expression of cytokine receptors. Vice versa, cytokines interfere with drug pharmacokinetics and pharmacodynamics through the interactions with cytochrome P450 and multiple drug resistance proteins. The aim of the review is to encourage more intensive studies in these fields of cytokine pharmacology. It also outlines major areas of searching promising candidates for immunotherapeutic interventions.
Keywords: Gene Expression Regulation; Drug Resistance; Receptors, Cytokine; cytokiny; signální transdukce; toll-like receptory; lymfocyty; léková rezistence; Pharmacokinetics; Signal Transduction; Immunotherapy; Toll-Like Receptors; systém (enzymů) cytochromů P-450; Animals; lidé; objevování léků; Cytochrome P-450 Enzyme System; Humans; Lymphocytes; zvířata; regulace genové exprese; farmakologie; makrofágy; receptory cytokinové; imunoterapie; Drug Discovery; Pharmacology; Cytokines; Macrophages; farmakokinetika